2013
DOI: 10.4103/0255-0857.115636
|View full text |Cite
|
Sign up to set email alerts
|

Study of the distribution of Malassezia species in patients with pityriasis versicolor and healthy individuals in Tertiary Care Hospital, Punjab

Abstract: M. globosa in its mycelial phase was the main etiological agent, but as normal flora from the back of healthy subjects, it was found in significantly less number (P = 0.01), suggesting that the higher pathogenicity of M. globosa in terms of enzymatic endowment, might be the cause of its predominance in PV lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 21 publications
1
35
0
1
Order By: Relevance
“…In Kuwait, population density of dogs is low and keeping them as pets is rare, whereas domestic and stray cats are not uncommon. A recent study from north-west India (Punjab) reported that about 5% of the isolates of M. pachydermatis were obtained from the back of healthy individuals without evidence of pityriasis versicolor [17]. This observation is noteworthy as it suggests that M. pachdermatis fungemia may also have similar mode of acquisition as for candidemia.…”
Section: Discussionmentioning
confidence: 96%
“…In Kuwait, population density of dogs is low and keeping them as pets is rare, whereas domestic and stray cats are not uncommon. A recent study from north-west India (Punjab) reported that about 5% of the isolates of M. pachydermatis were obtained from the back of healthy individuals without evidence of pityriasis versicolor [17]. This observation is noteworthy as it suggests that M. pachdermatis fungemia may also have similar mode of acquisition as for candidemia.…”
Section: Discussionmentioning
confidence: 96%
“…The highest detection rates of M. globosa is in agreement with studies from Iran Korea and Spain and stands in contrast with the other studies from India Canada and Russia in which they reported M. sympodialis as the commonest species, Bosnia and Herzegovina as M. restricta and Iran as M. furfur from normal healthy skin. 15,14,25,19,12,16,18 The differences between this study and others may not only be due to the result of variation in species on the skin of individuals in different countries, but also by the difference in sampling methods i.e. ; swabbing, a relatively insensitive method, scraping or adhesive transparent tape method, difference in culture media used (SDA with olive oil, mDA, LNA) and difference in incubation temperature of inoculated culture media.…”
Section: Discussionmentioning
confidence: 68%
“…16,17 Studies done in healthy Iranian, Indian and Tunisian healthy normal subjects yielded lower rate of colonization ranging from 31.2%-43%. [18][19][20] This study revealed only pure cultures of a single Malassezia isolated from one site in healthy individuals. This is in variance with a study done on Tunisian healthy normal subjects in which (13.32%) showed mixed cultures of different Malassezia spp including M. globosa + M. sympodialis (4.44%), M. globosa +M.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…2 In lesional skin the most common species are M. globosa, M. restricta, M. furfur and M. sympodialis. 3,4 A study has found it to be the second most common superficial fungal infection with 25.2% of the 9335 subject with superficial fungal infections presenting with pityriasis versicolor. 5 Of the total cases of pityriasis versicolor 31% were seen to involve the pediatric age group of children below 14 years of age.…”
Section: Introductionmentioning
confidence: 99%